Discharge characteristics of atmospheric pressure inductively coupled plasmas operating at 9; 27 and 50 MHz - Gunter, W. H.(Willem Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1984.